Targeted Expression of Cre Recombinase Provokes Placental-Specific DNA Recombination in Transgenic Mice - Zhou, Cissy Chenyi (Public Library of Science, 2012)
BACKGROUND: Inadequate placental development is associated with a high incidence of early embryonic lethality and serious pregnancy disorders in both humans and mice. However, the lack of well-defined trophoblast-specific gene regulatory elements has hampered investigations regarding the role of specific genes in placental development and fetal growth. PRINCIPAL FINDINGS: By random assembly of placental enhancers from two previously characterized genes, trophoblast specific protein α (Tpbpa) and adenosine deaminase (Ada), we identified a chimeric Tpbpa/Ada enhancer that when combined with the basal Ada promoter provided the highest luciferase activity in cultured human trophoblast cells, in comparison with non-trophoblast cell lines. We used this chimeric enhancer arrangement to drive the expression of a Cre recombinase transgene in the placentas of transgenic mice. Cre transgene expression occurred throughout the placenta but not in maternal organs examined or in the fetus. SIGNIFICANCE: In conclusion, we have provided both in vitro and in vivo evidence for a novel genetic system to achieve placental transgene expression by the use of a chimeric Tpbpa/Ada enhancer driven transgene. The availability of this expression vector provides transgenic opportunities to direct the production of desired proteins to the placenta.